1995
DOI: 10.1002/aic.690410524
|View full text |Cite
|
Sign up to set email alerts
|

Ternary microemulsions as model disordered media

Abstract: The ternary microemulsion systems alkane/water/DDAB (didodecyldimethylammonium bromide) form ideal model‐disordered media. The static microstructure is described by a simple parameter‐free model that can be predetermined and agrees with SAXS and SANS scattering experiments. The component volume fraction can be varied to exhibit bicontinuous random structures with a predicted percolation transition to disconnected water‐in‐oil droplets. Structural transitions are analyzed in the context of theories of percolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[85]. The important observation is knowing that head group area is fixed then the entire microstructure can be predicted by simple global packing constraints, in agreement with NMR, conductivity and neutron scattering [86][87][88][89][90].…”
Section: Phase Diagrams In Ternary Microemulsionsmentioning
confidence: 83%
“…[85]. The important observation is knowing that head group area is fixed then the entire microstructure can be predicted by simple global packing constraints, in agreement with NMR, conductivity and neutron scattering [86][87][88][89][90].…”
Section: Phase Diagrams In Ternary Microemulsionsmentioning
confidence: 83%
“…Recently we showed that a class of ternary microemulsions provides such a system [13,14]. By tuning experimental variables one can realize a disordered "porous" medium with specific prescribed microstructures.…”
mentioning
confidence: 99%
“…Cubic phases of zero average curvature can pack at surfactant parameters around and above 0.8, and cylinders with junctions probably correspond to the onset of connected random disordered phases. These are ubiquitous in cationic microemulsions where curvature is a delicate balance of oil penetration into surfactant tails. ,, …”
Section: Resultsmentioning
confidence: 99%
“…These are ubiquitous in cationic microemulsions where curvature is a delicate balance of oil penetration into surfactant tails. 29,49,50 Finally, there are two further mechanisms that promote the formation of branchpoints: (i) this process requires a partial dehydration of the polar headgroups and some hydrating water molecules are pushed back into the bulk aqueous phase (with an increment in entropy), and (ii) when the concentration of branches increases, the semispherical endcaps can fuse together to form a continuous cylindrical bridge that connects different rods. In the present system, the formation of connections is strongly suggested by the following experimental observations:…”
Section: Resultsmentioning
confidence: 99%